Didactics in initial teacher education: teaching practice report - Fortunato, Ivan (2018)
This paper was written in the form of an essay based on the experiments carried out in the teaching of the didactics course of the fifth semester of the undergraduate physics-teaching course, and of the second semester of the specialization in informatics applied to education, both from the Federal Institute of São Paulo, campus of Itapetininga, Brazil. Under the concept of educational “missions”, the didactic discipline, at both levels of education, was carried out almost entirely outside the Federal Institute, taking place in the field of teaching, that is, in schools. In the second half of 2017, we were in two state schools, being one of technical education, and one municipal school developing various teaching activities both in physics and computer teaching. In the end, it can be seen that the missions not only serve to bring schools closer to the place of teacher education, but also undergraduate and graduate students themselves can better understand the pedagogical theory, be its gaps or its ideas of reflection.